Optimizing the culture of Plasmodium falciparum in hollow fiber bioreactors. - Preechapornkul, P; Chotivanich, K; Imwong, M; Dondorp, A; Lee, S; Day, N; White, N; Pukrittayakamee, S (2010)
The hollow fiber bioreactor (HFBR) is a cell culturing system allowing continuous perfusion of medium. It was designed to grow microorganisms in a dynamically altering medium mimicking change in the in vivo intravascular and extravascular compartments. The cell compartment (extra capillary space) and medium compartment (intra capillary space) are connected through pores of semipermeable fiber membranes. These membranes allow exchange of gas and nutrients. We have adapted this system for the ex vivo culture of Plasmodiumfalciparum at high parasite densities. A Thai P. falciparum isolate (TM036) cultured in RPMI, supplemented with 0.5% Albumax II, could be maintained continuously in the system by daily changes of a small volumes of medium. Under optimized conditions the HFBR cultures attained 8% parasitemia in 40% hematocrit, thereby providing a total parasite biomass of 6.0 x 10(9) parasitized erythrocytes. The main problem encountered was clogging of micropores in the hollow fiber system by cellular debris over time. Although 'reverse flushing' partly prevented this, a larger pore size might be needed to overcome this problem. The system opens new possibilities for the study of in vitro drug sensitivity under conditions mimicking in vivo pharmacokinetics, and the selection of anti-malarial drug resistance and associated parasite biological and genomic changes.